2009
DOI: 10.1021/bi901550p
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in the Nicotinic Acetylcholine Receptor during Gating and Desensitization

Abstract: The nicotinic acetylcholine receptor (nAChR) is a member of the important Cys-loop ligand-gated ion channel superfamily that modulates neuronal excitability. After responding to their agonists, their actions are terminated either by removal of ligand or by fast and slow desensitization, processes that play an important role in modulating the duration of conducting states and hence of integrated neuronal behavior. We monitored structural changes occurring during fast and slow desensitization in the transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…4). This is not unexpected, considering that multiple conformers with subtle differences can coexist in a functional state (43,44). The sensitivity of ␤2 and insensitivity of ␣7 to the dynamics modulation by isoflurane are in good agreement with their distinctly different functional responses to isoflurane inhibition.…”
Section: Resultssupporting
confidence: 65%
“…4). This is not unexpected, considering that multiple conformers with subtle differences can coexist in a functional state (43,44). The sensitivity of ␤2 and insensitivity of ␣7 to the dynamics modulation by isoflurane are in good agreement with their distinctly different functional responses to isoflurane inhibition.…”
Section: Resultssupporting
confidence: 65%
“…8). (Chiara et al, 2009b), or whether there is preferential, transient binding to a nonchannel site (Arevalo et al, 2005;Yamodo et al, 2010).…”
mentioning
confidence: 99%
“…Time-resolved affinity labeling showed that the fast-and slow-desensitized states are structurally distinct (4), and electrophysiological recordings suggest that the multiexponential desensitization processes apply to other pLGICs (5). Overall, those data were represented by a minimal four-state (at least) allosteric model in which a central intermediate state accounts for fast desensitization (2,(6)(7)(8).…”
mentioning
confidence: 97%